Pregled in predstavitev dela z uporabniki s posebnimi potrebami v Valvasorjevi knjižnici Krško - Šalamon, Anja (Knjižnica, 2018)
Purpose: Work with special-needs users at Valvasor Library Krško is presented. In addition, the meaning of such work for all participants was researched. Methodology/approach: Two methods were used: the survey and the interview. The sample included 39 users with special needs involved in the project called "Living and Rejoicing with my Library", 7 employees from the institutions cooperating with Valvasor Library Krško and 13 employees from Valvasor Library Krško. The data obtained was later on analyzed and presented. Results: The research results show a high success rate of the project %Living and Rejoicing with my Library%. According to the interviewees working at the institutions which take care of people with special needs, users with special needs have made progress in all areas and their attitude towards books and reading has changed; this was noticed also by a librarian working with special-needs users at Valvasor Library Krško. Satisfaction has been expressed by both sides. When it comes to meeting the needs of special-needs users, the library is limited by an inadequate access to the building and poorly organized facilities. The new building will also bring better opportunities for the inclusion of such users into the activities of the library. Research limitations: The sample includes only users with special needs already cooperating with the library. Originality/practical implications: The results are useful not only for Valvasor Library Krško, but also for the institutions involved in the project, other public libraries and institutions uniting people with special needs that decide to cooperate.
Keywords: public libraries; special-needs users; splošne knjižnice; uporabniki s posebnimi potrebami; Valvasor Library Krško; Valvasorjeva knjižnica Krško